The sponge crabs of Western Australia and the Northwest Shelf with descriptions of new genera and species (Crustacea: Brachyura: Dromiidae) - Mclay, Colin L.; Hosie, Andrew M. (Zootaxa, 2022)
The Dromiidae of Western Australia are summarized primarily based on specimens from the collection of the Western Australian Museum and some additional material from the Australian Museum, Sydney. The genus Alainodromia McLay 1998, is recorded from Camden Sound, Australia, as a new species Alainodromia dambimangari sp. nov. New evidence suggests that the species of Alainodromia are very likely shell carriers that also have direct development. Five species of Cryptodromia are reported from Western Australia and a new genus, Baccadromia gen. nov., is erected for Dromia (Cryptodromia) bullifera Alcock, 1900. The genus Lamarckdromia Guinot & Tavares, 2003 is revised and now includes three species: L. beagle sp. nov., L. excavata (Stimpson, 1858) and L. globosa (Lamarck, 1818). Six species of Dromiidae are new to Australia: Baccadromia bullifera (Alcock, 1900), Cryptodromia amboinensis (De Man, 1888), C. pileifera Alcock, 1901, Epigodromia rotunda McLay, 1993, and Foredromia rostrata McLay, 2002. New records for Western Australia include: Cryptodromia hilgendorfi De Man, 1888, Epigodromia areolata (Ihle, 1913) and Lewindromia unidentata (Rüppell, 1830). A total of 31 species of dromiid crabs are now known from Western Australian coast with five species endemic to the state. There are more than 40 species of Dromiidae known from Australia of which about 40% are endemic.